Reconstruction of the Upper Slope Conditions of an Extraordinary Hydro-Meteorological Event Along the Jamapa Glacier Drainage System, Citlaltépetl (Pico de Orizaba) Volcano, Mexico - Sieron, Katrin; Weissling, Blake; Morales-Martínez, Marco Aurelio; Teran, Sergio (Frontiers in Earth Science, 2021)
A singular precipitation event on the summit glacial slopes of Mexico’s highest volcanic peak, Citlatépetl (also known as Pico de Orizaba), associated with the passage of Hurricane Ernesto across the southern Mexico mainland in August 2012, resulted in a debris flow at altitudes above 4400 m asl, culminating in a hyperconcentrated flow downstream that had major impacts to a river valley’s channel morphology as well as to communities along a 25 km runout. The lahar originated at the terminal moraine and proglacial ramp of the Little Ice Age (LIA) extent of Citlaltépetl’s Jamapa glacier. Precipitation amounts were estimated based on nearby CONAGUA stations, but also on TRMM satellite images leading to an estimated 106 mm for a 3 day total, with 85 mm (80% of the total) falling on Aug 9th, the date when the lahar event occurred. The initial debris flow removed a minimum estimated 60,000 m3 of material from the proglacial ramp. A possible causative scenario is that the precipitation event overpressured the groundwater hydrology of an already unstable glacial-melt-saturated moraine. We demonstrate a methodology for the recreation of a pre-event landscape and the environmental conditions at the onset of the lahar, utilizing satellite products, in-situ geomorphological and geological evidence, and UAS technology.